Pengenalan Edupreneur melalui Kegiatan Bazar bagi Anak Usia Dini di TK Aqidah Palangka Raya - Khairunnisa, Khairunnisa; Bismillah, Alfi; Miyani, Rizki; Mupadiah, Ana; Aghnaita, Aghnaita; Muzakki, Muzakki (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article discusses the importance of edupreneur activities for early childhood at TK Aqidah Palangka Raya. The activity aims to instill entrepreneurial values through practical experiences, such as a fruit-cutting sale bazaar that involves active participation from children. By applying the service learning method, student interns from IAIN Palangka Raya introduce the concept of edupreneurship to the children, helping them 2 understand transactions and the value of money. This research shows that entrepreneurship education not only teaches business skills but also builds character and independent mentality in children.